Neonatal Jaundice Risk Factors and Multidirectional Intensive Phototherapy Management at Azadi Teaching Hospital in Kirkuk City - Laylani, Amal Adnan; Hameed, Numan Nafie; Al-Azzawy, Muhannad Abdullah (South Eastern European Journal of Public Health, 2024)
Background: A common illness in infants, neonatal jaundice is caused by high bilirubin levels in the first few days of life, which results in yellowing of the skin and eyes. Aim: This study aims to explore neonatal jaundice risk factors and assess the efficacy of multidirectional intensive phototherapy management at Azadi Teaching Hospital in Kirkuk City. Patients and Methods: In this retrospective cross-sectional study spanning from April 1st, 2021, to October 1st, 2021, a total of 497 newborns were examined. Jaundiced neonates underwent intensive phototherapy utilizing the Bilisphere 360 system, which featured a chamber with 16 cylindrical, blue TL 20W/52 fluorescent tubes. The newborns were positioned on a gauze hammock suspended at the chamber's center, illuminated on all sides. Results: A study found that neonatal jaundice affects 50.70% of studied neonates, primarily in the 16-21-day age group, with males accounting for 57.95% of the sample. 94.84% of neonates experience jaundice due to ABO blood group incompatibility and 88.10% due to Rh incompatibility. Additionally, 77.78% of term deliveries are associated with jaundice. Infants with jaundice have higher Thyroid Stimulating Hormone (TSB) and Thyroid Stimulating Hormone (TSH) levels and a younger mean age compared to non-jaundiced infants. Bilisphere 360 proves significantly more effective in the critical 12 to 48 hours after admission, with a mean total bilirubin of 10.71 ± 1.01 mg/dl compared to 14.65 ± 1.71 mg/dl for Neonatal Exchange Transfusions (P-Value: 0.001). Factors like blood group incompatibility, labor duration, and birth weight influence TSB levels in jaundiced neonates. The Bilisphere 360 method is found to be more effective in managing neonatal jaundice than Neonatal Exchange Transfusions in reducing total bilirubin levels.